Estudos bioquímicos e análise de atividade enzimática em mioglobinas nativas e recombinantes de moluscos do gênero Biomphalaria - Kadima Nayara Teixeira (2010)
Myoglobin is one of the most studied and characterized hemeprotein. The focus in this protein with approximately 15-17 kDa has a relevant justification; spite of the solid data about myoglobin, this protein increasingly presents versatility in its function in the organism, and itcould play an indirect role in appearing and establishing pathologies.Pathologies related with myoglobin can range from membrane lipids peroxidation to serious hepatopathologies. Some pathologies are related with the capability of myoglobin to acquired oxidase activity after an interaction with exogenous agents as alkyl halides, or endogenous agents exemplified by hydrogen peroxide which is normally produced by cellular metabolism. Previous studies showed that it was necessarie a specific tyrosine residue presence to covalently bind heme group at mioglobin proteic part to acquires oxidase activity after being transformed using hydrogen peroxide; distal histidine e histidine residue 97 are recquired for oxidase activity if alkys halide are used. In this work, oxidase activity was not observed in Biomphalaria myoglobins treated withCCl4, according to previous studies about the necessecity of specific histidines, which are not present at Biomphalaria myoglobins; residual oxidase activity observed in these myoglobins before the treatment, was lost. After the hydrogen peroxide treatment oxidase activity wasobserved in Biomphalaria myoglobins. These myoglobins have no tirosine residues; it is suggested that another amino acid residue could be evolved in the reaction mechanism to provide oxidase activity. Some biochemical parameters of these myoglobins were obtained experimentally (molecular mass, isoeletric point, etc). During analysis it was detected the presence of myoglobin in the stomach, and not only in radular muscle as described in the literature. In both radular and stomach tissues the colour due to myoglobin is different, and according with the quantification of the myoglobin content and autoxidation rates, it is possible that the myoglobins in these two organs could be isoforms.